Cone Beam Computed Tomography Used in the Assessment of the Alveolar Bone in Periodontitis - Alexandra Mihaela Stoica; Monica Monea; Ramona Vlad; Dragos Dan Sita; Mircea Buruian (European Scientific Journal, ESJ, 2016)
Objectives: The aim of our study was to highlight the advantages of using Cone Beam Computed Tomography in the study of the extent of the alveolar bone loss, compared to the conventional intraoral radiography and to prove the boon of the CBCT scans for establishing the correct periodontal diagnosis. Material and methods: A total of 16 patients with age between 35-55 years old, and a minimum of 8 teeth per dental arcade, presenting peridontal clinical symptomatology were selected. We used a custom periodontal chart that included the measuring of the gingival recession and the pocket depth in 6 points for 16 teeth, 8 maxillary teeth and 8 mandibulary teeth in all cases. For the radiographic evaluation we used CBCT imaging and intraoral radiography. Results: CBCT scans offers the possibilities of measuring with accuracy the alveolar bone loss on mesial, distal vestibular and oral sides. It provides images with the exact position of the bone and also the expediency to assess the correct diagnosis. Retroalveolar radiography offers just a hint of the possible position of the alveaolar bone in all cases the anatomical details were offered by CBCT. Conclusions: A correct periodontal diagnosis using conventional radiography is not possible because of the superimposition of the anatomical structures. The importance of CBCT imaging is no longer disputed, at the present time it is the best radiographic investigation available.